Intrapancreatic Accessory Spleen: The Usefulness of Arciform Arterial Enhancement for non-Invasive Diagnosis - Low, Gavin (JOP. Journal of the Pancreas, 2012)
No abstract available. Image: Arciform arterial enhancement at axial arterial-phase contrast enhanced MRI.